Dolutegravir-induced liver injury leading to sub-acute liver failure requiring transplantation: a case report and review of literature. (March 2018) - Wang, Bo; Abbott, Laura; Childs, Kate; Taylor, Chris; Agarwal, Kosh; Cormack, Ian; Miquel, Rosa; Suddle, Abid
A patient with human immunodeficiency virus-1 infection presented with sub-acute liver failure, temporally related to commencement of an antiretroviral therapy regimen containing dolutegravir (Triumeq). The patient was not a carrier of HLA-B5701, and abacavir hypersensitivity was unlikely. We believe this is the first report of severe dolutegravir-related hepatotoxicity resulting in sub-acute liver failure and transplantation and highlights a potential need for closer monitoring after drug initiation.